Forgoing life support: How the decision is made in European pediatric intensive care units - Devictor, D.; Latour, Jos (2011)
Purpose: To determine how decisions to forgo life support are made in European pediatric intensive care units (PICUs). Methods: A multicenter, prospective study, the Eurydice II study, among 45 PICUs: 20 in France, 21 in Northern/Western (N/W) European countries and 4 in Eastern/Central (E/C) Europe. Data were collected between November 2009 and April 2010 through a questionnaire. Results: The decision to forgo life-sustaining treatment was made in 166 (40.6%) out of 409 deceased children (median 42.9%, France 38.2%, N/W European countries 60.0%, E/C European countries 0%; P < 0.001). In the E/C group, more patients died after cardiopulmonary resuscitation (CPR) failure than after forgoing life support (P < 0.001). In all PICUs, caregivers discussed the decision during a formal meeting, after which the medical staff made the final decision. The decision was often documented in the medical record (median 100%). The majority of the parents were informed of the final decision and were at the bedside during their child's death (median 100%). Decision to forgo life-sustaining treatment occurred in 40.6% of children, compared with 33% in Eurydice I. A high percentage of parents from France were now informed about the meeting and its conclusion as compared with Eurydice I (median 100%). Conclusions: The results of this study and comparison with the Eurydice I study (2002) show a trend towards standardization of end-of-life practices across N/W European countries and France in the past decade.